Oxidative status and the response to pegylated-interferon alpha2A plus ribavirin in chronic genotype 4 HCV hepatitis - Ahmed, Mohammed Mahmound; Abdel-Salam, Omar M. E.; Mohammed, Nadia A.; Habib, Dawoud Fakhry; Gomaa, Hewida Ez-eldin (Technische Universität Dortmund, 2013)
Oxidative stress may play a pathogenic role in chronic hepatitis C (CHC). The present study examined the oxidative status in plasma of patients with CHC who received pegylated interferon and ribavirin therapy. The following groups were included: (1) sustained virological response (28 patients), (2) null response (26 patients), (3) breakthrough (24 patients), (4) relapse (24 patients), (5) spontaneous cure (23 patients) and (6) twenty five normal subjects as a control group. Markers of oxidative stress including plasma malondialdehyde, nitric oxide, reduced glutathione, total antioxidant capacity and uric acid as well as serum ALT, AST, alkaline phosphatase, total bilirubin, albumin, prothrombin time were studied. The study indicated significant decline in reduced glutathione and total antioxidant capacity and markedly elevated levels of malondialdehyde and nitric oxide in all groups compared with the controls. Null response group had the highest levels of malondialdehyde and nitric oxide. Nitric oxide was significantly higher in those with null response compared with all other groups and with control subjects. Uric acid was significantly higher in spontaneous cure group compared with all other groups and with the controls. We concluded that CHC patients had increased oxidative stress. The oxidative status in plasma of these patients was not changed by antiviral therapy. The study also showed an important contribution of nitric oxide in null response patients. High serum uric acid did not interfere with the response and/or did not predict the response to antiviral therapy.
EXCLI Journal ; Vol. 12, 2013
Keywords: chronic hepatitis C; interferon; oxidative stress; 610